Investigating the Mechanism of Cyclodextrins in the Treatment of Niemann‐Pick Disease Type C Using Crosslinked 2‐Hydroxypropyl‐β‐cyclodextrin. Issue 46 (20th October 2020) - Carradori, Dario; Chen, Hsintsung; Werner, Beat; Shah, Aagam S.; Leonardi, Chiara; Usuelli, Mattia; Mezzenga, Raffaele; Platt, Frances; Leroux, Jean‐Christophe
Abstract: Niemann‐Pick disease type C (NPC) is a severe disorder that is characterized by intracellular transport abnormalities leading to cytoplasmic accumulation of lipids such as cholesterol and sphingolipids. The compound 2‐hydroxypropyl‐β‐cyclodextrin (HPβCD) has high cholesterol complexation capacity and is currently under clinical investigation for the NPC treatment. However, due to its short blood half‐life, high doses are required to produce a therapeutic effect. In this work, stable polymerized HPβCD is generated to investigate their in vitro mechanisms of action and in vivo effects. Crosslinked CDs (8–312 kDa) display a ninefold greater cholesterol complexation capacity than monomeric HPβCD but are taken up to a lower extent, resulting in an overall comparable in vitro effect. In vivo, the 19.3 kDa HPβCD exhibits a longer half‐life than the monomeric HPβCD but it does not increase the life span of Npc1 mice, possibly due to reduced brain penetration. This is circumvented by the application of magnetic resonance imaging‐guided low intensity‐pulsed focused ultrasound (MRIg‐FUS), which increases the brain penetration of the CD. In conclusion, stable polymerized HPβCDs can elucidate CDs' mechanism of action while the use of MRIg‐FUS warrants further investigation, as it may be key to harnessing CDs full therapeutic potential in the NPC treatment. Abstract : The 2‐hydroxypropyl‐β‐cyclodextrin (HPβCD) is a well‐established pharmaceutical excipient that can complex cholesterol and is currently under clinical investigation to treat Niemann‐Pick disease type C (NPC). However, high doses of the drug are needed to achieve a therapeutic effect. Using stable and long circulating crosslinked HPβCDs, this study attempts to further understand the mechanisms behind CDs' activity.